The handbook of European structured financial products - Fabozzi, Frank J.; Choudhry, Moorad (Frank J. Fabozzi series., 2004)
The first comprehensive account of the European structured financial products market. This comprehensive survey of the securitization market in Europe covers all asset-backed securities (the major classes and some nonconventional asset classes that have been securitized), residential and commercial mortgage-backed securities, collateralized debt obligations, and more. Frank J. Fabozzi, PhD, CFA, CPA (New Hope, PA), is the Frederick Frank Adjunct Professor of Finance in the School of Management at Yale University. Prior to joining the Yale faculty, he was a Visiting Professor of Finance in the.